The epidemiology of edentulous atrophic mandibular fractures in Europe. Issue 12 (December 2019) - Brucoli, Matteo; Boffano, Paolo; Romeo, Irene; Corio, Chiara; Benech, Arnaldo; Ruslin, Muhammad; Forouzanfar, Tymour; Rodríguez-Santamarta, Tanía; de Vicente, Juan Carlos; Tarle, Marko; Dediol, Emil; Pechalova, Petia; et al.
Abstract: Introduction: The objective of the present study was to assess the demographic variables, causes, and patterns of edentulous atrophic fractures of the mandible managed at several European departments of oral and maxillofacial surgery. The results of this multicenter collaboration over a 10-year period are presented. Methods: The data of all patients with fractures of the atrophic edentulous mandible from the involved maxillofacial surgical units across Europe between January 1, 2008, and December 31, 2017 were recorded: gender; age; voluptuary habits; comorbidities; etiology; fracture sites; synchronous body injuries; atrophy of the mandible according to Luhr classification; eventual type of treatment; timing of the eventual surgery; length of hospital stay. Results: A total of 197 patients (86 male and 111 female patients) with 285 mandibular fractures were included in the study. Mean age of the study population was 75 years. Statistically significant associations were found between Luhr classes I – II and condylar fractures on one hand (p < .0005), and between Luhr class III and body and parasymphyseal fractures on the other hand (p < .05). Finally, 135 patients underwent open reduction and internal fixation, 56 patients did not undergo any intervention, and 6 patients underwent closed reduction. No statistically significant association was observed between treatment, timing of treatment, comorbidities, and concomitant injuries. Conclusions: The management of edentulous atrophic mandibular fractures remains challenging. Treatment decisions should continue to be based on the clinician's previous experience and on the degree of bone resorption in edentulous mandible in relation to fracture subsites.